Optimalisasi Dampak Kesehatan Mental dari Interdependensi Ekonomi di ASEAN - Hadi, Cholichul (Kajian Psikologi dan Kesehatan Mental, 2024)
Purpose: This study investigates the impact of ASEAN’s deepening economic integration on workers’ mental health. This study focuses on transnational exposure through trade dependence and foreign direct investment (FDI)and its psychological consequences via job insecurity and cultural mismatch. Research methodology: Using cross-sectional survey data from 5,000 cross-border workers in six ASEAN countries, the research applies a multilayer network model combining (1) an economic exposure index (trade/GDP ratio and FDI inflows), (2) DSM-5-based anxiety and depression scales, and (3) moderated mediation testing for cultural buffers, particularly collectivism. Results: Findings show that Higher export-to-GDP ratios significantly predicted increased anxiety symptoms (? = 0.42, p < 0.001), fully mediated by precarious employment. Contrary to expectations, collectivism exacerbated stress among low-skilled workers (? = 0.21, p = 0.03). Network analysis further revealed bridging nodes linking economic sectors and mental health outcomes, thereby emphasizing systemic interdependence. Conclusions: ASEAN economic interdependence generates measurable psychological costs for labor, particularly through insecure employment arrangements in Malaysia. Rather than mitigating stress, cultural collectivism may intensify pressure in vulnerable conditions. Limitations: The cross-sectional design restricts causal inference, and self-reported measures may carry bias. Broader longitudinal and qualitative approaches are required to validate these findings. Contribution: This study provides the first empirical evidence of macroeconomic-mental health linkages in the ASEAN region. This highlights the necessity of policy interventions, including selective de-growth strategies, in sectors heavily reliant on external trade to protect worker well-being.